Sensitization Towards Aerosol Optical Properties And Radiative Forcing, Real Case In Morocco - Ssouaby Somia (EDP Sciences, 2021)
Mineral dust is one of the most important aerosol components in the Earth’s atmosphere. Desert aerosol constitute the main types of tropospheric aerosols whose optical property uncertainties are still quite important. In this study, we analyse the variability of aerosol optical depth (AOD), Angstrôm Exponent (α), Single Scattering Albedo (ω0) and aerosol radiative forcing (ARF) of desert aerosol recent measurements, for six AERONET sites covering the belt desert areas: Ouarzazate (Morocco), Tamanrasset (Algeria), El Farafra (Egypt), Mezaira (Unites Arab Emirates), Kuwait University (Kuwait), Dalanzadgad (Mongolia). The annual cycle of the aerosol optical depth dialy averages shows variable values due to the changeable weather and the Sahara source. The highests were recorded at the Sahara site (2.2 at Tamanrasset) and (2.9 at Kuwait-University). The spectral single scattering albedo SSA annual averages varies in the interval (0,8-0.95) indicating dominant scattering. Desert aerosol radiative forcing shows always a negative ARF with a maximums registred in July, -90 W/m2 at surface (Mezaira) and -26 W/m2 at the top of the atmosphere (Kuwait) that imply a general trend towards regional warming of the total column atmosphere with a maximum near +55 W/m2 observed in July at UAE.